Evaluation of psychological stress, awareness, and attitude regarding COVID-19 infection pandemic within senior citizen homes in Kanpur, Uttar Pradesh: An online pioneer survey - Rohan Sachdev; Kriti Garg; Mehrotra Vishal; Kriti Nigam; Samiksha Shwetam (Wolters Kluwer Medknow Publications, 2021)
CONTEXT: Senior citizens with comorbidities are more vulnerable to severe illness and associated high mortality rate due to the prevailing pandemic. AIMS: The aim of this online survey is to evaluate the psychological stress, awareness, and attitude regarding COVID-19 and the infection control measures taken by the senior citizens. SETTINGS AND DESIGN: The present study involves an online descriptive cross-sectional questionnaire survey conducted at a senior citizen home. SUBJECTS AND METHODS: The questionnaire of the study consists of 20 questions and was performed among 84 older adults of two senior citizen homes supervised by nongovernment organizations through video conferencing on WhatsApp. STATISTICAL ANALYSIS USED: Participant's response was calculated and expressed as percentages and frequency, with the mean values. RESULTS: Seventy-one percent of senior citizens responded to the study, and 91.6% accepted phobic anxiety due to COVID-19 lockdown, while 97.6% reported behavioral disorders. Majority of the senior citizens (96.4%) had awareness regarding COVID-19 infection, 97.6% were aware of water and hand sanitization, while 98.8% of the respondents had a positive response toward COVID-19 protection practice in the future. CONCLUSIONS: The awareness regarding COVID-19 was found to be satisfactory among the senior citizens, although psychological counseling and more precautions are required to make them feel secure from the current pandemic scenario.